Ketahanan Pangan pada Rumah Tangga Petani di Kabupaten Timor Tengah Selatan, Nusa Tenggara Timur - Anita Christina Sembiring; Lalu Juntra Utama; Astuti Nur (Perum BULOG, 2026)
Background: Household food security is an important determinant of family welfare and nutritional status, particularly in rural areas with high poverty rates. The Food Consumption Score (FCS) is widely used to assess food security based on the diversity and frequency of food consumption, but its application in dry and chronically food-insecure areas such as South Central Timor (SCT) Regency is still limited. Objectives: This study aims to analyze the food security of farming households using the FCS approach and examine food consumption patterns based on the FCS classification in SCT Regency. Methods: This study used a cross-sectional design in farming households with toddlers. Primary data were collected through interviews with mothers of toddlers using a structured questionnaire. The variables studied included household characteristics (parental education and number of family members), frequency of consumption of eight food groups, and FCS scores calculated according to World Food Programme (WFP) guidelines. Results and Discussion: The results showed that classification using the WFP standard cut-off categorized the majority of households as food secure. However, when using the adjusted cut- off in previous research, 97.1% of households were classified as food insecure. Consumption patterns are dominated by cereals and vegetables, with very limited consumption of animal protein sources, nuts, and milk. Conclusion: No significant association was found between parental education or family size and food security status. These findings suggest the potential for overestimating food security if only using the global FCS cut-off without considering the local context. The results of this study can serve as a basis for formulating more contextual food and nutrition interventions in rural dryland areas